2012
DOI: 10.1002/cncr.27757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massachusetts health insurance reform on mammography use and breast cancer stage at diagnosis

Abstract: BACKGROUND:Massachusetts law requires all residents to maintain a minimum level of health insurance, and rates of uninsurance in that state decreased from 6.4% in 2006 to 1.9% in 2010. The authors of this report assessed whether health insurance expansion was associated with use of mammography and earlier stage at breast cancer diagnosis. METHODS: By using a prereform/postreform design with a concurrent control (California), mammography rates in the last year were assessed using the Behavioral Risk Factor Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Keating and colleagues reported that expansion of coverage in Massachusetts did not result in an increase of mammography screening or earlier cancer diagnosis. 10 Although our study does not address rates of breast cancer diagnosis, the results indicate that with expansion of Medicaid, these important reconstructive procedures were provided more frequently to this already underserved population. Patients with breast cancer who did not believe they had adequate health care coverage before expansion might not have pursued reconstructive surgery even after implementation of the WHCRA, and having Medicaid coverage might have alleviated some of those concerns.…”
Section: Discussionmentioning
confidence: 79%
“…Keating and colleagues reported that expansion of coverage in Massachusetts did not result in an increase of mammography screening or earlier cancer diagnosis. 10 Although our study does not address rates of breast cancer diagnosis, the results indicate that with expansion of Medicaid, these important reconstructive procedures were provided more frequently to this already underserved population. Patients with breast cancer who did not believe they had adequate health care coverage before expansion might not have pursued reconstructive surgery even after implementation of the WHCRA, and having Medicaid coverage might have alleviated some of those concerns.…”
Section: Discussionmentioning
confidence: 79%
“…[6][7][8] Across all income groups in Massachusetts, data from the BRFSS show that mammography use declined during our study period between 2004 and 2010 and could not be directly attributed to healthcare reform practices. 9 It is possible that the sustained high access to mammography screening we observed, which was available via Commonwealth Care insurance in this low-income population, reflects low financial barriers to care, 10 including the absence of physician-visit copayments. Importantly, in the diverse population we studied here, we note that a high percentage of women, particularly Hispanic and non-Hispanic Asian populations, required safety-net funds to pay for their preventive care.…”
Section: Discussionmentioning
confidence: 95%
“…Screening rates may have changed relative to the counterfactual of what rates would have been in the absence of health reform. Keating et al () compare mammography rates before and after Massachusetts reform relative to rates in California and do not find increases in mammography. Their study was limited by the short time period considered pre‐reform and post‐reform and the choice of California, which differs from Massachusetts in geography and population demographics, as a control state.…”
Section: Introductionmentioning
confidence: 99%